Envolvimento dos canais para cálcio tipo-L na resposta cardiodepressora do farnesol em coração de rato - Souza, Diego Santos de (2016)
The farnesol (C15H26O) is a sesquiterpene alcohol found in herbs and essential oils. Research show some beneficial properties of farnesol as: antioxidant, anti-inflammatory and chemopreventive properties. However, the farnesol futher inhibition of activity of L-type calcium channels in smooth muscle. This study sought to analyze the involvement of calcium channels L-type in the cardiodepressant farnesol response in the rat heart. To this, contractile studies were conducted on left atria drawn to rest tension 5mN (0,5gf) and subjected to field stimulation with above-threshold current pulses of the 1 Hz, kept in isolated organ vessel, submerged in Krebs-Henseleit solution (8 mL) and aerated with carbogênica mixture (95% O2 and 5% CO2). The atrial contraction force was capture by an isometric transducer. Electrocardiographic recordings were performe on isolated heart, aortic perfusion under a constant flow (10 ml / min) Langendorff type system. The hearts were keep spontaneously beating, to determine the heart rate, and in heart stimulated were determined PR interval (PRI), QT (QTi) and complex QRS. Left ventricular pressure was determined in the heart stimulated electrically by means of a balloon inflated with water at a pressure of 15 cmHg. In rat left atrium, the farnesol response to the contraction strength showed a negative inotropic effect, reducing the contraction force at 41.63% at the maximum concentration used, with an EC50 of 2.84 ± 0.19 mM. To evaluate the effect of farnesol of the positive inotropic response of CaCl2 and (±)-Bay K8644 was observed that the farnesol shifted to the right CaCl2 concentration-response curve and decreased maximum efficiency (100% to 23%) and abolished curve of (±)-Bay K8644. TEA was use to evaluate the role of K+ channels in the negative inotropic response and the maximum effect by farnesol (41.63 to 63.02%) was increased. In isolated heart, there was an increase of PRI, QTi and QRS complex, and reduced left ventricular pressure (37, 38%) and heart rate (25.22%). Thus, farnesol exerts inotropic and negative chronotropic responses in the heart by reducing current to the L-type Ca2+.